Reconstruction of post-traumatic long bone defect with vascularised free fibula: A series of 28 cases - Gurdayal Singh Kalra; Pradeep Goel; Pradeep Kumar Singh (Indian Journal of Plastic Surgery, 2013)
Introduction: The severe long bone defects usually follow high-energy trauma and are often associated with a significant soft-tissue injury. The goal of management of these open long bone defects is to provide stable fixation with maintenance of limb length and soft-tissue coverage. The purpose of this article is to present the clinic-radiological outcome, complications and treatment of post-traumatic long bone defect with vascularised fibula transfer. Materials and Methods: Retrospective records of 28 patients were analysed who presented with post-traumatic long bone defects and in whom reconstruction with vascularised free fibula was done. Demographic data were recorded and clinical and radiological assessment was done. Results: Out of 28 patients in whom vascularised free fibula transfer was carried out three flaps were lost while non-union occur in three patients. Three patients developed a stress fracture of transferred free fibula in the post-operative period. Few of the patients experienced some problems in the donor leg; however, all of them improved in subsequent follow-up. Discussion: It is clearly evident from this study that timing of surgery plays an important role in the micro-vascular reconstruction in trauma cases. All the complication like flap loss, non-union or delayed union occur in patients in whom reconstruction was delayed. Conclusion: The free vascularised fibula graft is a viable method for the reconstruction of skeletal defects of more than 6 cm, especially in cases of scarred and avascular recipient sites or in patients with combined bone and soft-tissue defects. Results are best when the reconstruction is done within 1 week of trauma.